Effectiveness of the Merdeka Belajar Policy: Challenges and Opportunities in Improving the Quality of Primary and Secondary Education in Indonesia - Mulyo Prayitno; Moh Rosyid Mahmudi (Balai Publikasi Indonesia, 2025)
This research explores the effectiveness of the Merdeka Belajar policy in improving the quality of primary and secondary education in Indonesia as well as the challenges and opportunities faced in its implementation. Through a qualitative approach using the case study method, data was collected from in-depth interviews with teachers, school principals, and Education Service officials in several regions, as well as through analysis of policy documents and related literature. The research results show that this policy provides opportunities to improve the quality of education, especially in developing 21st-century skills such as critical thinking, collaboration, and creativity. However, there are significant obstacles in its implementation, especially related to the infrastructure gap between schools in urban and rural areas and the readiness of teachers to adopt innovative learning methods. The digital divide and limited access to training are the main obstacles that have the potential to weaken educational inequality in Indonesia. Therefore, government support in the form of funding, equitable infrastructure development, and ongoing training is very necessary to ensure that the Merdeka Belajar policy can be implemented effectively and evenly. Thus, this policy has the potential to create a more inclusive and relevant education system if these challenges can be overcome